Partitions and Atoms of Clause Structure - Sportiche, Dominique (Routledge Leading Linguists, 1998)
This collection brings together some of Dominique Sportiche's best work, including essays that are published here for the first time. The articles discuss the architecture of syntax in natural languages and Sportiche suggests that languages do not differ at all in their syntactic organization. This view takes shape through the analysis of a variety of syntactic configurations and essays examine what it means to be a Subject, how Case marking functions, how it relates to Agreement, and how Pronominal Clitic Constructions should be analyzed.